Increased frequency of systemic pro-inflammatory Vδ1+ γδ T cells in HIV elite controllers correlates with gut viral load. Issue 1 (December 2018) - Olson, Gregory; Moore, Sarah; Richter, James; Garber, John; Bowman, Brittany; Rawlings, Crystal; Flagg, Meaghan; Corleis, Björn; Kwon, Douglas
Abstract γδ T cells predominate in the intestinal mucosa and help maintain gut homeostasis and mucosal immunity. Although HIV infection significantly alters these cells, what drives these perturbations is unclear. Growing evidence suggests that impaired intestinal immune function in HIV leads to chronic immune activation and disease progression. This occurs even in HIV controllers – individuals with undetectable HIV viremia without antiretroviral therapy (ART). We show that Vδ1+ cells, a subset of γδ T cells described as being important in intestinal barrier function, increase in frequency in HIV-infected individuals, including HIV controllers. These cells resemble terminally differentiated effector memory cells, producing the pro-inflammatory cytokines IFNγ, TNFα, and MIP-1β upon stimulation. Importantly, pro-inflammatory Vδ1+ cell frequency correlates with levels of HIV RNA in intestinal tissue but not in plasma. This study supports a model in which local viral replication in the gut in HIV controllers disrupts the phenotype and function of Vδ1+ cells, a cell type involved in the maintenance of epithelial barrier integrity, and may thereby contribute to systemic immune activation and HIV disease progression.